New Hybrid Conjugate Gradient Method as a Convex Combination of PRP and RMIL+ Methods - HADJI, Ghania; LASKRI, Yamina; BECHOUAT, Tahar; BENZINE, Rachid (Studia Universitatis Babeș-Bolyai Mathematica, 2024)
The Conjugate Gradient (CG) method is a powerful iterative approach for solving large-scale minimization problems, characterized by its simplicity, low computation cost and good convergence. In this paper, a new hybrid conjugate gradient HLB method (HLB: Hadji-Laskri-Bechouat) is proposed and analysed for unconstrained optimization. By comparing numerically CGHLB with PRP and RMIL+ and by using the Dolan and More CPU performance, we deduce that CGHLB is more efficient. Mathematics Subject Classification (2010): 90C26, 65H10, 65K05, 90C26, 90C06. Received 08 October 2021; Accepted 12 September 2022